Deodorization process of vegetal soybean oil using Thermomechanical Multi-Flash Autovaporization (MFA). (15th September 2022) - Jamoussi, Bassem; Jablaoui, Cherif; Hajri, Amira K.; Chakroun, Radhouane; Al-Mur, Bandar; Allaf, Karim
Abstract: Conventional deodorization for refining vegetable oil involves evaporating volatile molecules by applying high temperatures (240–260 °C) for 2–3 h. It inevitably leads to a degradation of the refined oil quality. The chief volatile compounds from the conventional deodorization process were hydrocarbons, which are not the odor source of the oil. Particularly in the case of crude soybean oil, the main compounds responsible odor were Nonanal, Decanal, E-2-hexenal, and 2-Undecenal. The present study adopts the innovative technology of Multi-Flash Autovaporization "MFA" to effectively remove the compounds mainly responsible for the smell and taste while preserving the oil quality. It eradicates the concerned volatile molecules present in crude soybean oil. Based on experimental studies, we used phenomenological mathematical models to describe the deodorization, estimate the reaction efficiency, and optimize the correlation between thermodynamical data (volatility) and the evolution of these molecules during deodorization process. By optimizing the processing parameters, we experimentally estimated the MFA processing parameters at 800 kPa of saturated steam for 60 s, followed by an instant pressure-drop towards a vacuum of 5 kPa. The volatile ratio became 92% lower. Preserving tocopherol levels and the profile of the principal fatty acids significantly reveals the preservation of the oil quality. Highlights: Thermomechanical Multi-Flash Autovaporization (MFA) is used for the first time for deodorization vegetable oil. Elimination of compounds that create an unpleasant odor and taste, while preserving the quality of the oil. Identification and quantification of the most volatile compounds in crude soybean oil.